Modifying the Response of Male Broiler Chickens to Heat Stress Through Early Age Feed Restriction and Thermal Conditioning - Liew, Pit Kang (2002)
Two experiments were conducted to investigate the effects of early age feed restriction and heat conditioning on tolerance to acute and chronic heat stress in male broiler chickens. In both experiments, equal numbers of chickens were subjected to (i) 60% feed restriction on day 4, 5, and 6 (FR), (ii) exposure to 36±IoC and 50-60% relative humidity for 1 hour from day 1 to 21 (HT), (iii) 60% feed restriction on day 4, 5, and 6 and exposure to 36± l oC and 50-60% relative humidity for 1 hour from day 1 to 21 (FRHT). (iv) ad libitum feeding and no heat treatment (control). In experiment I, on day 35, all birds were exposed to 39± l oC for 6 hours and 50% relative humidity. Subjecting chicks to FR, HT and FRHT reduced HLR response to the heat challenge. Following heat exposure, the FR and FRHT chick had greater heat shock protein (hsp) 70 density than those of controls. The hsp 70 response of HT birds was not significantly different from the other three groups. The FRHT birds were more hyperthermic than controls during heat challenge. In experiment II, from day 36- 50, all birds were exposed to 38± l oC and 80 % relative humidity for 2 hours/day. One day following heat exposure (day 37), all birds were administrated intranasally with infectious bursal disease (IBD) vaccine virus. The dosage used was l Ox of the recommended level. Subjecting chicks to FRHT improved relative weight gain and resistance to IBD infection and reduced HLR in response to the heat treatment as compared with the control birds. Although there is evidence that FR and HT can improve heat tolerance, the FRHT combination may further enhance the ability of birds to withstand chronic heat stress. The acquired improved heat tolerance resulting from FRHT, FR, and HT could be attributed to enhanced hsp 70 response. The trend of hsp 70 response correlated well with IBD lesion scores, suggesting hsp 70 may play a role in resistance against viral infection. Based on experiment I and II, it can be concluded that the present findings confirmed earlier studies that FR is effective in alleviating the adverse effects of heat stress. Subjecting birds to FRHT can further improve tolerance to chronic but not acute heat stress.